A Prospective Study on the Detection of Gastric Neoplasms Using Pepsinogen and Gastrin-17 Levels - Sun-Young Lee; Hee-Won Moon; Yeon-Sun Ahn; Joo Hye Song; Jeong Hwan Kim; In-Kyung Sung (Gut and Liver, 2025)
Background/Aims : GastroPanel tests include gastrin-17 (G-17) levels in addition to pepsinogen (PG) and Helicobacter pylori serology tests. The aim of this study was to identify significant test findings in patients with gastric neoplasms by comparing the findings of GastroPanel tests and conventional serum PG assays. Methods : Consecutive individuals who underwent serological testing were included from May 2023 to August 2024. Foreigners and those with gastrectomy, renal insufficiency, previous H. pylori eradication, and recent acid suppressant use were excluded. Results : Among the 1,101 participants, 122 were diagnosed with gastric neoplasms. High G-17 levels (odds ratio [OR], 1.030; 95% confidence interval [CI], 1.008 to 1.052), low I/II ratios determined by GastroPanel tests (OR, 0.834; 95% CI, 0.779 to 0.894), and low I/II ratios determined by HBI PG assays (OR, 0.584; 95% CI, 0.511 to 0.668) were significant variables for detecting gastric neoplasms. The cutoff values for low I/II ratios were <6.15 (GastroPanel test) and <3.005 (HBI assay), with no differences in diagnostic performance between the two tests (p=0.085). Although the I/II ratio alone was a significant independent variable for detecting early gastric cancers, advanced gastric cancers, adenomas, and neuroendocrine tumors, the G-17 level alone was significant only for adenomas and neuroendocrine tumors. The findings of the patients with gastrointestinal stromal tumors did not differ from those of the controls. Conclusions : Blood test findings are useful for detecting gastric neoplasms, except for gastrointestinal stromal tumors. The addition of G-17 levels to PG tests is only beneficial for diagnosing gastric neoplasms associated with corpus atrophy, such as adenoma and neuroendocrine tumors (ClinicalTrials.gov identifier NCT05883345)